Promoting Equitable Scholarship Literacy through an Integrated Webinar Series on the Tatra Academy Digital Platform - Khairunnas Khairunnas; Syahrul Alamsyah; Hilyatul Mustafidah; Husnatul Mahmudah (Sarau Institute, 2025)
Unequal access to international scholarship information remains a significant barrier in Indonesia. This community service program aimed to promote equitable scholarship literacy through a digital mentoring approach via the Tatra Academy platform. The program followed four stages: needs identification via Instagram, resource planning, online implementation via Zoom and YouTube, and demographic evaluation. Analysis of 1,102 cleaned registrants revealed a broad nationwide reach, including participants from frontier and underdeveloped (3T) regions. The program demonstrated high inclusivity across generations, engaging 369 participants under age 20 and 34 participants over age 40, supporting lifelong learning. The initial session on Hungary and Poland scholarships recorded the highest enthusiasm, followed by the AAS/MANAKI series and technical guides for essays and CVs. Findings show that digital platform integration effectively overcomes geographic barriers, democratizes information access, and supports inclusive human resource development.